Parents’ Social Representations of institutions of child and adolescent after school care (Práxis Educativa, 2017)
This article describes the Social Representations (SR) that parents of children and adolescents have of the role of family, school and social after school care and of moral development. The study was developed in social after school care institutions in a city in the State of Paraná which attend 250 at-risk children and adolescents. Data was collected in interviews carried out with the parents or other adults in charge of these children and adolescents (N=60). The description of most common SR was based on the analysis of information, images and attitudes supplied by the interviewees. The research revealed that the school is seen as something useful in the future for work purposes; the after school care is seen as an extension of the home care and ancillary of the domestic moral education; and the domestic educational process is seen as correction of errors and moral deviations. Keywords: Social after school care. Family. Moral education.